2020
DOI: 10.3389/fimmu.2019.03131
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Selection of Duck Primary Cells as Pathogenic and Innate Immunologic Cell Models for Duck Plague Virus

Abstract: Duck plague virus (DPV) is a representative pathogen transmitted among aquatic animals that causes gross lesions and immune inhibition in geese and ducks. The mechanism of organ tropism and innate immune evasion of DPV has not been completely deciphered due to a lack of cell models to study the innate immune manipulation and pathogenicity of aquatic viruses. In the present study, we isolated five types of duck primary cells [duck embryo fibroblasts (DEFs), neurons, astrocytes, peripheral blood mononuclear cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, no obvious changes in these genes were detected (data not shown). Our previous study has shown that the basal expression level of STING, RIG-I, MDA5, MAVS, IRF7, IFN-β, and MX in monocytes or macrophages was higher than that in DEF cells, neurons, and astrocytes ( Tian et al., 2019 ). Hence, we hypothesized that SC75741 may promote innate immunity responses relying on the basal level of these genes.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…However, no obvious changes in these genes were detected (data not shown). Our previous study has shown that the basal expression level of STING, RIG-I, MDA5, MAVS, IRF7, IFN-β, and MX in monocytes or macrophages was higher than that in DEF cells, neurons, and astrocytes ( Tian et al., 2019 ). Hence, we hypothesized that SC75741 may promote innate immunity responses relying on the basal level of these genes.…”
Section: Resultsmentioning
confidence: 96%
“…We further determined whether SC75741 could inhibit virus infection in different duck cell types. For this reason, we isolated duck primary neurons, astrocytes, and monocytes or macrophages as previously described ( Tian et al., 2019 ). We observed that the viral titers of VSV-GFP ( Figure 4 A) and DTMUV ( Figure 4 B) were reduced in duck neurons and astrocytes under the addition of SC75741 as in the DEF cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data was analyzed by one-way ANOVA. ***p < 0.001 and persistently infects monocytes/macrophages [68], but the mechanism of immune evasion by DEV is unknown. In our study, we first found that DEV pUL47 significantly inhibits the IFN-β signalling induced by poly(I:C) and downregulates the STAT1-induced ISG expression.…”
Section: Discussionmentioning
confidence: 99%